Nonword repetition errors of children with and without specific language impairments (SLI) - Burke, Heidi L. (Int J Lang Commun Disord, 2014)
BACKGROUND: Two ubiquitous findings from the literature are that (1) children with specific language impairments (SLI) repeat nonwords less accurately than peers with typical language development (TLD), and (2) all children repeat nonwords with frequent phonotactic patterns more accurately than low-probability nonwords. Many studies have examined repetition accuracy, but little work has examined children’s errors. AIMS: To examine nonword repetition errors from a previously published study in terms of phonotactic probability. METHODS & PROCEDURES: Eighteen children with SLI (mean age = 9;2) and 18 age-matched controls (mean age = 8;11) repeated three- and four-syllable nonwords. Substitutions were analysed in terms of phoneme frequency and phonotactic probability of the syllable containing the substitution. OUTCOMES & RESULTS: Results for all children show that phoneme substitutions generally involved replacement with more frequently occurring phonemes. Also, the resulting phonotactic probability within syllables containing substitutions was greater than the probability of the targets. This trend did not differ by group. CONCLUSIONS & IMPLICATIONS: These results suggest that both children with SLI and children with TLD substitute less frequent phonemes with more frequent ones, and less probabilistic syllables with higher probability ones.